Managing digital finance: The role of cryptocurrency in financial reporting - Yusuf, Muh. Fathir Maulid; Rauf , Dian Mayafaty; Hamid, Ahmad; Sultraeni, Wiwin; Garusu, Ilham Akbar (Edelweiss Applied Science and Technology, 2024)
This study aims to explore the role of cryptocurrency in corporate financial reporting amidst the rise of digital finance. The research adopts a descriptive-analytical design, utilizing both qualitative and quantitative methods. Data were collected from literature reviews, interviews with financial practitioners, and case studies of companies integrating cryptocurrencies into their financial operations. The findings highlight that while cryptocurrencies offer opportunities for portfolio diversification and faster cross-border transactions, they also introduce challenges, such as price volatility and regulatory uncertainty, which complicate asset valuation and risk management in financial statements. The study reveals that companies like Tesla and MicroStrategy have reported increased asset values due to cryptocurrency investments, but also faced difficulties in providing consistent financial estimates due to market fluctuations. The research concludes that clear regulatory frameworks and enhanced accounting standards are essential for transparent and reliable financial reporting. Practical implications include the need for financial practitioners to develop expertise in cryptocurrency valuation and risk management while ensuring compliance with international financial reporting standards.